2016
DOI: 10.23986/afsci.57343
|View full text |Cite
|
Sign up to set email alerts
|

Annual variation in sensory characteristics of seventeen apple cultivars

Abstract: Sensory characteristics of 17 apple cultivars commonly grown in Finland were compared over three harvest years (2009)(2010)(2011). Descriptive analysis with a trained panel (n = 11-14) comprised 17 attributes rated from 0 ('not at all') to 10 ('very'): four appearance (green, red, area of red colour, skin waxiness), three odour (intense, grassy, fruity), five texture (hard, crispy, mealy, juicy, tough peel), and five flavour (intense, sour, sweet, astringent, diverse) attributes. Ratedintensities differed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…() as “an amalgamation of influences that include climate, landscape (slope, exposure, and the biological and physical environment), soil, and geology.” Also, the sensory profile can vary due to harvest/slaughter time and storage period (Elgar, Watkins, Murray, & Gunson, ; Horsted, Henning, & Hermansen, ). Furthermore, there is a seasonal effect, for example, Bunning, Kendall, Stone, Stonaker, and Stushnoff () concluded that differences among lettuce cultivars have larger impact than growing season on sensory profiles, Lynch, Koppel, and Reid () concluded that seasonal differences have a larger impact on black walnut cultivars than cultivar on sensory profiles, and Seppä, Tahvonen, and Tuorila () concluded that even though harvest year have effect on the apples sensory profiles, the effect varies due to the variety. In this study, we do not provide an overview of the interacting influence of weather conditions and handling from field to fork impact on the sensory characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…() as “an amalgamation of influences that include climate, landscape (slope, exposure, and the biological and physical environment), soil, and geology.” Also, the sensory profile can vary due to harvest/slaughter time and storage period (Elgar, Watkins, Murray, & Gunson, ; Horsted, Henning, & Hermansen, ). Furthermore, there is a seasonal effect, for example, Bunning, Kendall, Stone, Stonaker, and Stushnoff () concluded that differences among lettuce cultivars have larger impact than growing season on sensory profiles, Lynch, Koppel, and Reid () concluded that seasonal differences have a larger impact on black walnut cultivars than cultivar on sensory profiles, and Seppä, Tahvonen, and Tuorila () concluded that even though harvest year have effect on the apples sensory profiles, the effect varies due to the variety. In this study, we do not provide an overview of the interacting influence of weather conditions and handling from field to fork impact on the sensory characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…A short growing season and insufficient summer heat combined with unfavorable winter conditions are the main indicators that limit the cultivation of high-quality apple cultivars in the south-west of Finland and in the central zone of Russia (Kaukoranta et al 2010, Krasova et al 2013. According to Seppä et al 2016 during the growing season the average air temperature for many years in Helsinki is 13.8 °C, while in the Orel region it is 15.4 °C (by 1.6 °C more) the amount of precipitation for this period is 309 and 312 mm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…'Petteri' had a consistently sweet fruit taste, while 'Samo', 'Make' and 'Vuokko' have a good sweet and sour taste. Seppä et al (2016) reported about a consistent taste of late-ripening fruits under various annual climatic conditions. For ex.…”
Section: Discussionmentioning
confidence: 99%